Analysis of changes in composites after different level of heat exposure - Chua, HongWei (2014)
Carbon fiber is heavily used in the aviation industry and its mechanical strength is always an important property to investigate. It is always crucial to determine heat damage in the carbon fiber accurately to avoid disastrous event from happening. One of the popular extended non-destructive testing used by the aviation industry to determine heat damage in carbon fiber is the 4100 ExoScan. 4100 ExoScan’s manufacturer, the Agilent’s Technologies had published a research paper named “Composite thermal damage – correlation of short beam shear data with FTIR spectroscopy” to show the effectiveness of 4100 ExoScan to characterize the heat damage in carbon fiber. However, there are some questions arising from the accuracy of 4100 ExoScan in predicting the heat damage in carbon fiber. This report examines the ability of 4100 ExoScan to predict the presence of heat damage in carbon fiber accurately. The results show incompetency of 4100 ExoScan in predicting heat damage in carbon fiber accurately and it will be discussed in detail in the report.